Chronic heart failure in intensive care unit: can we accurately predict the risk?. (14th October 2021) - Maltes, S; Maltes, S; Rocha, B.M.L; Cunha, G.J.L; Lopes, P; Moura, A; Aguiar, C.M.T; Coelho, F; Torres, J; Santos, P; Monteiro, F; Lamas, T; et al.
Abstract: Background: Severity of disease scoring systems, namely the Simplified Acute Physiology Score (SAPS) and Acute Physiology and Chronic Health Evaluation (APACHE), are widely used to predict mortality in Intensive Care Units (ICU). Yet, neither score includes chronic HF in their model. We aimed to evaluate whether these scores perform well in risk prediction of death of patients previously diagnosed with heart failure (HF). Methodology: This is a single-center retrospective cohort of patients admitted to an ICU in 2019. Those whose admission lasted <24 hours were excluded from analysis. The SAPS II and APACHE II scores were calculated using data from the first 24 hours of ICU admission, imputing the worst variable obtained within this timeframe. HF was defined according to the ESC recommendations. In order to assess the performance of the scores, Receiver Operating Characteristic (ROC) Curves were used to predict the risk of death in ICU in HF compared to the non-HF population. Results: A total of 267 patients were hospitalized in ICU for a period over 24 hours in 2019 (mean age 67±16 years; 58.8% males; 21.7% with chronic HF; 33.7% admitted for sepsis). Compared to patients without HF, those with chronic HF were older (74±13 vs. 65±16 years; p<0.001) and had higher risk scores (mean SAPS II: 43.2±21.7 vs. 56.5±20.7; p<0.001; mean APACHE II: 19.8±10.0 vs. 25.1±10.0; p<0.001). Moreover, these patients were at higher risk of meaningful events during hospitalization (e.g. acute kidney injury: 38.0 vs. 66.1%; p<0.001; shock at any time: 52.4 vs. 67.8%; p=0.036). Furthermore, patients with HF had a trend towards higher mortality rates in ICU (17.3 vs. 28.8%; p=0.051) and a significantly higher death in overall hospitalization (30.8 vs. 45.8%; p=0.032). ROC curves performed well in predicting the risk of ICU death regardless of HF (SAPS II – AUC 0.78 vs. 0.81; p=0.36; APACHE II – AUC 0.75 vs. 0.78; p=0.37). Conclusion: Approximately 1 in every 4 patients admitted to the ICU had chronic HF. Traditional risk scoring systems (SAPS II and APACHE II) performed well regardless of HF. While these results are reassuring as far as risk stratification accuracy is concerned, HF patients remained at a higher risk for worse outcomes. Therefore, prognostic tools with a therapeutic clinical applicability are urgently needed to improve the outcome of this population. Funding Acknowledgement: Type of funding sources: None.